How is the Principal’s Leadership Style to Improve the Quality of Graduates? (Learning from Madrasah Aliyah Negeri 1 Yogyakarta) - Nora Saiva Jannana; Fika Amini (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
This study aims to describe the leadership style of madrasah principals used to improve the quality of graduates of MAN 1 Yogyakarta. The existence of the principal is a form of leadership in educational institutions. The head of a madrasah has an essential role in improving the quality of graduates and the success of education in madrasahs. This research is a case study with a qualitative approach. Purposive sampling is applied for this research. The data were collected by observation, interviews, and documentation study. Data analysis techniques use transcript, coding, grouping, comparing, and contrasting. The data validity technique was used through technique and source triangulation. This study shows that the leadership style of the head of MAN 1 Yogyakarta is democratic-charismatic leadership. The leadership of the director of a madrasah has a significant portion in the effort to improve the quality of graduates at MAN 1 Yogyakarta. The leadership style provides the most outstanding contribution to the sustainability of resource management in schools.